The evolution of monetary policy in Latin American economies: Responsiveness to inflation under different degrees of credibility - Stefan Gießler (Halle Institute for Economic Research (IWH), 2020)
This paper investigates the forward-lookingness of monetary policy related to stabilising inflation over time under different degrees of central bank credibility in the four largest Latin American economies, which experienced a different transition path to the full-fledged inflation targeting regime. The analysis is based on an interest rate-based hybrid monetary policy rule with time-varying coefficients, which captures possible shifts from a backward-looking to a forward-looking monetary policy rule related to inflation stabilisation. The main results show that monetary policy is fully forward-looking and exclusively reacts to expected inflation under nearly perfect central bank credibility. Under a partially credible central bank, monetary policy is both backward-looking and forward-looking in terms of stabilising inflation. Moreover, monetary authorities put increasingly more priority on stabilising expected inflation relative to actual inflation if central bank credibility tends to improve over time.
urn:nbn:de:gbv:3:2-121596
Keywords: C32; E42; E58; 330; forward-lookingness; central bank credibility; inflation targeting; hybrid monetary policy rule; time-varying coefficients